The Intervention of Effective Playdough Activity on The Increase of Cognitive Development of Autistic Children - Yusuf, Ah.; Ummam, Aulia Faridatul; Nastiti, Aria Aulia; Yunitasari, Esti (International Journal of Psychosocial Rehabilitation, 2020)
Cognitive delay is one of the problems that occur in autistic children. If not immediately addressed, the children’s cognitive ability will not develop properly. One of the stimulations to improve the cognitive abilities of autistic children is by playing. This study aimed to examine the effect of the intervention of playdough activity on the cognitive development of autistic children. This study applied a quasi-experiment method using the pretest-posttest control group design. The population of this study was all autistic children in one foundation in Surabaya. The number of samples was 16 children, namely eight children for the treatment group and eight children for the control group. Data were analyzed using the Wilcoxon signed-rank test and Mann-Whitney U test with the significance level α = 0.05. The intervention of playdough activity had a significant effect (ρ = 0.014). By giving the intervention of playdough activity, it can improve the cognitive development of autistic children. The playdough activity trains children to recognize the colors and shapes of fruit or animal. They are also taught to make shapes. They can also communicate and interact well during the activity.